The role of extreme events in formation the relief and sediments of the marginal zone of the Widawka lobe near Radomsko, Central Poland - Frydrych, Małgorzata; Rdzany, Zbigniew (Acta Geographica Lodziensia, 2024)
The article presents the features of the relief and the details of the internal structure of the marginal zone near Radomsko shaped during the maximum extent of the Wartanian Glaciation. This section is exceptional because it preserves well--defined classical forms of the marginal zone: terminal depressions, asymmetric terminal moraines, and sandurs through which meltwater flowed into the marginal valley, which at that time represented the parallel segment of the pra-Warta. Research focused on the section of the marginal zone in the Adamów village has shown that rhythmic accumulation of meltwater with erosional incidents and gravitational flows within the terminal moraines and proximal sandurs played an important role in its formation. This area documents one of the few examples of glacial flood beyond the reach of the Vistulian (Weichselian) Glaciation. The record of flood is almost exclusively fossil, as well as unique structures in sandur deposits that can be interpreted as gravel dunes. The area was also shaped by dynamic advances of the ice-sheet resulting in local glaciotectonic deformation.